The customer preferences on product quality of Abian Tubuh Tofu - ilhamudin, Muhammad; Masrun (ProBisnis : Jurnal Manajemen, 2024)
This study aims to determine the quality of food sector SME products that are widely spread in Mataram City. The focus of research is on tofu products which are one of the superior products in this city. This study used the survey sample method, by choosing the Abian Tubuh tofu industry center as the research location. The study population was all customers knew who came to make purchases at some predetermined traditional market. In determining respondents as data sources in this study, researchers used purposive sampling techniques. Because the number of members of the study population is not known with certainty, the number of research samples was determined at 100 respondents. To answer the problem posed, the analytical tool used is the Ideal-Point Model, which is a consumer evaluation of what is perceived with what is desired. This model measures the difference between what is perceived and what consumers want. The results showed that the quality of SME products tofu Abian Tubuh, Mataram City was very good. This is indicated by the quality value being in the upper interval class which means that the quality of the tempeh product is in accordance with consumer wishes.